Problem drinking and physical intimate partner violence against women: evidence from a national survey in Uganda - Tumwesigye Nazarius; Kyomuhendo Grace; Greenfield Thomas; Wanyenze Rhoda K (BMC, 2012)
Abstract Background Problem drinking has been identified as a major risk factor for physical intimate partner violence (PIPV) in many studies. However, few studies have been carried on the subject in developing countries and even fewer have a nationwide perspective. This paper assesses the patterns and levels of PIPV against women and its association with problem drinking of their sexual partners in a nationwide survey in Uganda. Methods The data came from the women's dataset in the Uganda Demographic and Health Survey of 2006. Problem drinking among sexual partners was defined by women's reports that their partner got drunk sometimes or often and served as the main independent variable while experience of PIPV by the women was the main dependent variable. In another aspect problem drinking was treated an ordinal variable with levels ranging from not drinking to getting drunk often. A woman was classified as experiencing PIPV if her partner pushed or shook her; threw something at her; slapped her; pushed her with a fist or a harmful object; kicked or dragged her, tried to strangle or burn her; threatened/attacked her with a knife/gun or other weapon. General chi-square and chi-square for trend analyses were used to assess the significance of the relationship between PIPV and problem drinking. Multivariate analysis was applied to establish the significance of the relationship of the two after controlling for key independent factors. Results Results show that 48% of the women had experienced PIPV while 49.5% reported that their partners got drunk at least sometimes. The prevalence of both PIPV and problem drinking significantly varied by age group, education level, wealth status, and region and to a less extent by occupation, type of residence, education level and occupation of the partner. Women whose partners got drunk often were 6 times more likely to report PIPV (95% CI: 4.6-8.3) compared to those whose partners never drank alcohol. The higher the education level of the women the less the likelihood of experiencing PIPV (ptrend < 0.001). Similar relationship was found between wealth status and experiencing PIPV. Conclusions Problem drinking among male partners is a strong determinant of PIPV among women in Uganda. PIPV prevention measures should address reduction of problem drinking among men. Longerterm prevention measures should address empowerment of women including ensuring higher education, employment and increased income.